READINESS OF FORMATION OF FUTURE TEACHERS TO THE PREVENTION OF CONFLICT SITUATIONS IN SECONDARY SCHOOLS BY MEANS OF ESTETOTERAPIYI - Muromets, Victoria H. (Educological discourse, 2015)
The article is analyzed the estetoterapy resources to promoting of formation for readiness of the future teachers to prevent and overcome conflicts in the educational environment. It carried out a theoretical analysis of the concept of «prevention», «estetotherapy»; discloses the potential use of estetotherapy in extracurricular activities as a preventive factor of conflict prevention in the educational environment.